Data and computer communications. - Stallings, William, 1945- (Upper Saddle River (N.J.) : Prentice Hall, 2004)
This timely revision of one of the all time best-selling Data Communications and Networking book features the clarity and scope of a Stallings classic. Ideal for professional reference or self-study, this comprehensive volume provides the most up-to-date coverage of the essential, need to know topics in data communications, networking, Internet technology and protocols, and standards. It emphasizes the critical role of performance in driving protocol and network design. Features a convenient modular format. This edition features a major expansion of wireless networking, network security, and related standards; as well as a new chapter on TCP/IP, and the latest developments in Quality of Service, and high speed LAN and WAN technology. Protocol Architecture. Data Transmission. Guided and Wireless Transmission. Signal Encoding Techniques. Digital Data Communication Techniques. Data Link Control. Multiplexing. Spread Spectrum. Circuit Switching and Packet Switching. Asynchronous Transfer Mode. Routing in Switched Networks. Congestion Control in Switched Data Networks. Cellular Wireless Networks. Local Area Network Overview. High-Speed LANs. Wireless LANs. Internetwork Protocols. Internetwork Operation. Transport Protocols. Network Security. Distributed Applications. For Product Development personnel, Programmers, Systems Engineers, Network Designers and others involved in the design of data communications and networking products.
Bibliogr., index, glossary
Keywords: Computer networks; Computernetwerken; Data transmission systems; Datatransmissienetwerken; Protocollen